Integrating the Concept of Situational Leadership and V.U.C.A. in Formulating Adaptive and Responsive Defense Policies - Aris Sarjito (Journal of Social Interactions and Humanities, 2023)
The effectiveness of defense policies is crucial in today's volatile, uncertain, complex, and ambiguous (V.U.C.A.) global security environment for maintaining national security. This study uses qualitative research and secondary data analysis. The study suggests that situational leadership principles can improve defense policies' effectiveness in V.U.C.A. environments, but challenges remain in integrating these theories. The research identifies barriers to change, including resistance, bureaucratic inertia, limited resources, and a lack of situational leadership training, necessitating understanding, capacity-building, interdisciplinary collaboration, and stakeholder engagement. Policymakers must prioritize agility, flexibility, and innovation in developing adaptive defense policies, incorporating situational leadership, effective communication, shared leadership, and continuous monitoring and evaluation.